Pluralisms - Marty, Martin E. (The annals of the American Academy of Political and Social Science, 2007)
Arguing that the move from “diversity” to “pluralism” in American discourse better matched some of the historical circumstances and social outcomes in American life, this article is designed to provide a framework for more detailed and close-up elaborations on the pluralist theme. As the field of study develops, it becomes ever more clear that no single definition will do justice to “diversity,” “multiculturalism,” and so on, so it is time to think of the “plural in the plural” and speak of “pluralisms.”